Labor Mobility, Trade and Social Capital - Maurice Schiff (Institute for the Study of Labor (IZA), 2004)
Labor market integration raises welfare in the absence of distortions. This paper examines labor and goods market integration in a general equilibrium model with social capital. The findings are: i) labor market integration has an ambiguous impact on welfare, and raises it if the goods produced and the labor skills are sufficiently different; ii) compared to Pareto optimum, labor mobility (social capital) is excessively large (depleted); iii) trade is superior to labor market integration if trading costs are no higher than private migration costs; otherwise the outcome is ambiguous; and iv) the creation of new institutions in response to labor market integration has an ambiguous impact on welfare.
Keywords: J61; F22; F16; Z13; 330; social capital; labor market integration; trade; Arbeitsmobilität; Arbeitsmarkt; Marktintegration; Wirtschaftsintegration; Social Capital; Aussenwirtschaft; Allgemeines Gleichgewicht; Wohlfahrtseffekt; Theorie